Sustainable business models for climate services provision – Learning from Senegal - Ouedraogo, Issa; Muriithi, Cyrus (2025)
This presentation examines sustainable business models for delivering Climate Information Services (CIS) in Senegal, drawing on CGIAR Climate Action research under AoW2 on digital advisories and climate risk management. It reviews the CIS value chain—generation, transfer, translation, and use—and assesses market opportunities across agriculture, livestock, fisheries, and finance. Using evidence from impact, utility, and willingness-to-pay studies, the analysis identifies viable public–private partnership models that bundle CIS with insurance, inputs, and advisory services. Results highlight strong demand but emphasize the need for localized, downscaled forecasts, cost-sharing mechanisms, and value-chain integration. The report concludes with practical pathways to scale CIS sustainably through private-sector engagement and institutional coordination.